The effects of innovation policies on firm level patenting - Marit E. Klemetsen (Statistics Norway, Research Department, 2015)
This paper examines the impacts of R&D tax credits and direct R&D subsidies on Norwegian firms' patenting, with a particular focus on environmental patenting. Whereas direct subsidies are aimed at projects with low private and high social return, tax credits do not discriminate between projects or technologies. We find that both direct subsidies and tax credits have significant positive effects on patenting in general. Although direct subsidies have triggered more patents, tax credits are more efficient in the sense that they have triggered more patents relative to the typical subsidy amount received. With regard to environmental patenting, we find no significant effects of tax credits, whereas the effects of direct subsidies are large and significant. A possible explanation is that environmental innovations face the environmental externality, greater knowledge externalities and require funding that is willing to take more risks and allow more patience. Tax credits currently favor small and medium sized firms and firms with relatively low R&D investments. For large firms, we find large and significant effects of direct subsidies, but no significant effects of tax credits.
Keywords: C54; D22; O31; O38; Q55; 330; R&D tax credits; SkatteFUNN; direct R&D subsidies; environmental innovation; SMEs; Poission count model; fixed effects